Toward three-dimensional hybrid inorganic/organic optoelectronics based on GaN/oCVD-PEDOT structures - Linus Krieg (Nature Portfolio, 2020)
Though integrating functional organic materials with semiconductor nanostructures is attractive for 3D chip processing, realizing these hybrids remains a challenge. Here, the authors report an oxidative chemical vapor deposition-based process for designing novel 3D hybrid optoelectronic structures.